Von fernen Frauen Beiträge zur lateinamerikanischen Frauen- und Geschlechtergeschichte - González de Reufels, Delia (Historamericana, 2022)
This volume brings together essays by women historians who deal with a wide range of topics and issues in Latin American women's and gender history. They range chronologically from the 16th to the 20th century, geographically from the Caribbean to Cono Sur.